Novel amphiphilic conjugates of p-tert-butylthiacalix[4]arene with 10, 12-pentacosadiynoic acid in 1, 3-alternate stereoisomeric form. Synthesis and chromatic properties in the presence of metal ions. (29th January 2018) - Burilov, Vladimir; Valiyakhmetova, Alsu; Mironova, Diana; Sultanova, Elza; Evtugyn, Vladimir; Osin, Yuri; Katsyuba, Sergey; Burganov, Timur; Solovieva, Svetlana; Antipin, Igor
Abstract : Functional polydiacetylene vesicles based on thiacalix[4]arene–10, 12-pentacosadiynoic acid conjugates showed selective colorimetric response toward lanthanide ions. Abstract : For the first time amphiphilic receptors based on the 1, 3- alternate stereoisomeric form of thiacalix[4]arene, bearing carboxyl/sulphonate polar headgroups on one side and 10, 12-pentacosadiynoic acid (PCDA) residues on another side of the macrocyclic plane, were synthesized. It was shown that embedding of synthesized macrocycles in PCDA vesicles results in stable colloids with a size around 300 nm. The temperature of ultrasonication before UV irradiation has a critical impact on the packing of vesicles for better polymerization. The increase of calixarene content in PCDA vesicles causes a decrease in the degree of PCDA polymerization. Nevertheless, calixarene additives dramatically change the colorimetric response of photopolymerized PCDA vesicles toward metal ions. Vesicles with 10 mol% content of calixarene have significant colorimetric response toward lanthanide ions with a detection limit up to 8 μM. The colorimetric response in the series of lanthanide ions depends on the ionic radius, and the greatest response was found for the largest La(iii ) ion. It was found that binding of calixarene–PCDA vesicles with lanthanide ions results in the formation of large 1 μm aggregates followed by sedimentation. Thus, the mechanism of colorimetric response of calixarene-decorated polydiacetylene vesicles toward lanthanide ions includes the distortion of the calixarene cavity provoking perturbation of the PDA backbone accompanied by metal-induced aggregation of functionalized vesicles with sedimentation of particles. Therefore, calixarene–PCDA vesicles have great potential for the future design of bifunctional colloids with sensor and separation applications.